PERSIDANGAN PIDANA SECARA ONLINE, RESPON CEPAT MA HADAPI PANDEMI COVID-19 - Wahyu Iswantoro (Program Magister Ilmu Hukum Universitas Pancasila, 2020)
The global pandemic of Virus Corona (Covid-19) in Indonesia gives impact to legalservice at judiciary institution under the Supreme Court of Indonesia. Due to the condition,The Supreme Court should make a policy about Work from Home (WFH) for the Judges andCourt Officers as a rolling. In urgent condition (force majeure), the courthouse should do thecourt proceedings with online or teleconference. As the fast response, The Supreme Courthad been made an innovation such as the Regulation Letter as legal fundament to do thecourt proceedings with online or teleconference. That policy legitimation by the principle of“Salus Populi Suprema Lex Esto” its mean “The society safety is the highest Law” (Cicero)